2010
DOI: 10.3945/jn.109.115253
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake Needed to Maintain Target Serum 25-Hydroxyvitamin D Concentrations in Participants with Low Sun Exposure and Dark Skin Pigmentation Is Substantially Higher Than Current Recommendations

Abstract: Cutaneous cholecalciferol synthesis has not been considered in making recommendations for vitamin D intake. Our objective was to model the effects of sun exposure, vitamin D intake, and skin reflectance (pigmentation) on serum 25-hydroxyvitamin D (25[OH]D) in young adults with a wide range of skin reflectance and sun exposure. Four cohorts of participants (n = 72 total) were studied for 7-8 wk in the fall, winter, spring, and summer in Davis, CA [38.5 degrees N, 121.7 degrees W, Elev. 49 ft (15 m)]. Skin refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(133 citation statements)
references
References 46 publications
7
124
1
1
Order By: Relevance
“…These include associations with CDAI, muscle function, fatigue, QoL, maintenance of epithelial barrier function, decreased hospitalisations, reduced risk of surgery and cancer. In terms of dosage required to achieve these levels 20-25μg (800-1000 IU)/d vitamin D 3 appears sufficient to achieve a serum level of 50 nmol/l, and between 25 and 100μg (1000 and 4000 IU)/d to bring levels beyond 75 nmol/l (on average 50μg (2000 IU)/d is required for this purpose (114)(115)(116)(117)(118)(119)(120)(121)(122)(123) ). In the present study of Crohn's disease patients, we found that 50μg (2000 IU)/d increased mean 25(OH)D levels to 91·6 (95% CI 75·5, 107·6) nmol/l over winter months, which was significantly higher than levels in the placebo group 40·4 (95% CI 30·4, 50·4) nmol/l (P < 0·001) (34) .…”
Section: Resultsmentioning
confidence: 99%
“…These include associations with CDAI, muscle function, fatigue, QoL, maintenance of epithelial barrier function, decreased hospitalisations, reduced risk of surgery and cancer. In terms of dosage required to achieve these levels 20-25μg (800-1000 IU)/d vitamin D 3 appears sufficient to achieve a serum level of 50 nmol/l, and between 25 and 100μg (1000 and 4000 IU)/d to bring levels beyond 75 nmol/l (on average 50μg (2000 IU)/d is required for this purpose (114)(115)(116)(117)(118)(119)(120)(121)(122)(123) ). In the present study of Crohn's disease patients, we found that 50μg (2000 IU)/d increased mean 25(OH)D levels to 91·6 (95% CI 75·5, 107·6) nmol/l over winter months, which was significantly higher than levels in the placebo group 40·4 (95% CI 30·4, 50·4) nmol/l (P < 0·001) (34) .…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, it is more readily accepted that humans are different from rats, as a species as well as in terms of weight for determining treatment doses, and that rickets prevention is not the only vitamin D action to be taken into account. The daily requirement does of course depend on what the optimal target 25-OH-D serum level is considered to be: for a 25-OH-D serum level of 50 nmol/liter, 800-1000 IU/day of vitamin D appears sufficient, but to bring most people above the 75 nmol/liter level, a dosage of between 1000 and 4000 IU/day (depending on the individual, but on average 2000 IU/day) is required [Heaney et al 2003a[Heaney et al , 2009Grant and Holick, 2005;Hollis, 2005;BischoffFerrari et al 2006BischoffFerrari et al , 2009bBischoffFerrari et al , 2012Vieth, 2006;Hall et al 2010;Schwalfenberg et al 2010;Whiting and Calvo, 2010;Cashman et al 2011;Garrett-Mayer et al 2012;Holick, 2011Holick, , 2012. However, vitamin D intake via (unfortified) food is very marginal in normal Western diets, even in those considered well balanced, and generally provides less than 100-200 IU/day, rarely reaching little more than 400 IU/day with fortified food [Calvo et al 2004;Moore et al 2005;Välimäki et al 2007;O'Donnell et al 2008;Vatanparast et al 2010;von Geldern and Mowry, 2012].…”
Section: Vitamin D Requirements and Insufficiencymentioning
confidence: 99%
“…34 Another 2010 study assessed the association among skin pigmentation, sun exposure, skin reflectance, vitamin D intake, and body surface area exposed to the sun. 35 The authors concluded that to maintain serum 25(OH)D levels of greater than 30 ng/mL, individuals of European ancestry with high sun exposure need a supplemental dietary intake of 1300 IU/d of vitamin D, whereas individuals of African ancestry with low sun exposure need 2100 to 3100 IU/d year round. 35 A recent study demonstrated that after broadband UV-B (290-320 nm) exposure in a laboratory setting, the increase in serum 25(OH)D levels was independent of the constitutive skin pigmentation of the studied individuals.…”
Section: Does Skin Pigmentation Affect Vitamin D Levels?mentioning
confidence: 99%
“…35 The authors concluded that to maintain serum 25(OH)D levels of greater than 30 ng/mL, individuals of European ancestry with high sun exposure need a supplemental dietary intake of 1300 IU/d of vitamin D, whereas individuals of African ancestry with low sun exposure need 2100 to 3100 IU/d year round. 35 A recent study demonstrated that after broadband UV-B (290-320 nm) exposure in a laboratory setting, the increase in serum 25(OH)D levels was independent of the constitutive skin pigmentation of the studied individuals. 36 This finding suggests that the innate vitamin D biosynthesis abilities of the skin of individuals of different pigmentation are similar.…”
Section: Does Skin Pigmentation Affect Vitamin D Levels?mentioning
confidence: 99%
See 1 more Smart Citation